Toxicity evaluation of vinasse and biosolid samples in diplopod midgut: heat shock protein in situ localization - Coelho, Maria Paula Mancini [UNESP]; Moreira-de-Sousa, Cristina [UNESP]; de Souza, Raphael Bastão [UNESP]; Ansoar-Rodríguez, Yadira [UNESP]; Silva-Zacarin, Elaine Cristina Mathias; Fontanetti, Carmem Silvia [UNESP] (Springer Nature, 2017)
Large amounts of residues generated by agricultural, urban and industrial activities are dumped daily on the soil. This practice deserves special attention because it causes serious environmental problems. This study evaluated the toxic potential of the sugarcane vinasse, a by-product of the sugar-alcohol industry, and the biosolid, a residue produced by wastewater treatment plants, both widely used as fertilizers. The evaluation was performed through bioassays using a typical soil bioindicator, the diplopod Rhinocricus padbergi. The specimens were exposed to soils containing these residues in concentrations that are compatible with the Brazilian regulation for agricultural use. Semi-quantitative immunolabelling analyses of the stress protein HSP70 were performed on the midgut of the studied diplopods. There was a significant increase in the immunolabelling of HSP70 proteins as a response to xenobiotics from both residues, particularly in regions where the function of the cells is the detoxification of the organ (e.g. the hepatic cell layer and specific regions of the epithelium). Higher immunolabelling was observed in the specimens exposed to vinasse in comparison with the biosolid exposure. This demonstrates that the substances in the tested residues had proteotoxic action in the exposed animals and induced a cytoprotective response, which led to higher stress protein immunolabelling. Therefore, caution is needed for the use of such residues in agriculture.
Keywords: Fertilizers; HSP70; Immunohistochemistry; Millipedes; R. padbergi; Soil toxicity